Atrial Myxoma – A treatable cause of congestive heart failure - Fonseca, A. G. (2007)
The authors report the case of a 53 year old woman presenting with sub-acute severe global heart failure and anaemia. Clinical investigation led to the diagnosis of a left atrial myxoma. There was complete recovery following surgical excision of the tumour. This case illustrates the fact that cardiac myxomas, although benign tumours, may be potentially very severe and underlines the fact that these tumours are treatable and a reversible cause of heart failure.